Effect of Students’ Worksheet Based on Scientific Approach in Listening Skills for the Tenth Grade of SMA Negeri 6 Medan - Adry Arizona; Azhary Tambusai (Medan Resource Center, 2023)
The objectives of this research are to know the effect of scientific approach in increasing students’ ability in listening skills in SMA Negeri 6 Medan. The method of this research is quantitative experimental. Population in this research is the first grade of SMA Negeri 6 Medan which are 120 students, and the sample are 60 students as group that applied the scientific approach. The result of this research found that the grade x students of SMA Negeri 6 Medan taught by stdents’ worksheet based on scientific approach in listening skills is good and after calculating and analyzing the data of the research, is found that the grade x students of SMA Negeri 6 Medan taught by students’ worksheet based on scientific approach in listening skills is fair and also the use of students’ worksheet based on scientific approach increase the students’ listening skills to the grade X students of SMA Negeri 6 Medan, it proved on the t-table with df 58 (n = n – 2 =30+30-2= 58) at t-critical 0.05 it obtained 1,67. If compared the value of t-tale (2,17>1,67). It stated that the hypothesis is accepted. It means that the grade X students of SMA Negeri 6 Medan which taught by students’ worksheet based on scientific approach in listening skills is higher than those without students’ worksheet based on scientific approach and there were some effectiveness of using students’ worksheet in teaching listening.